Tax avoidance in government-owned firms: Evidence from Italy. Issue 3 (3rd April 2019) - Mafrolla, Elisabetta
ABSTRACT: This paper studies whether and why government-owned firms avoid taxation to a greater extent than wholly privately-owned firms do. By considering a sample of Italian listed corporations for the period between 2006 and 2011, it was found that government ownership had a systematically negative effect on corporate effective tax rate, with a prevalence of tax-planning policies focused on the long term. Managers of local government-owned firms focused on minimizing costs, even if this was to the detriment of national tax-revenue collection. IMPACT: The author investigated tax avoidance in government-owned firms with the surprising finding that government owners avoid taxation to a greater extent than private sector owners. Managers of government-owned firms (and especially local government owners) were found to pursue political goals that focused on cost- minimizing policies, reducing national tax revenue. This paper will be of value to policy- makers, who should consider tax avoidance by government-owned enterprises as a real possibility.